Dilated Intercellular Spaces of Esophageal Epithelium among Malaysian With Nonerosive Reflux Disease: Transmission Electron Microscopic (Tem) study - Myint, Yi Yi; Tun, Ye; Mohammad Amjad, Nasser; Mat Hassan, Mohd. Zailani (2010)
Dilated intercellular space (DIS) is considered as early signs of acid damage to the esophageal epithelium. The diffusion of refluxed gastric acid into the intercellular space activates chemo sensitive nociceptors whose signals are transmitted via the spinal cord to the brain for symptom (heartburn) perception as well as initiated a short reflex arc to esophageal (longitudinal) smooth muscle as means of precipitating a sustained esophageal contraction. Objectives: This study aims to evaluate the intercellular space of oesophageal epithelium and to find out the association between clinical symptoms and DIS among Malaysian with NERD. Materials and methods: The study group included 8 NERD patients with reflux symptoms, normal mucosa on endoscopy and positive 24-hour pH monitoring and 5 normal controls. Specimens were routinely processed for transmission electron microscopy (TEM). The intercellular spaces between prickle cells were viewed and their widths were determined by TEM. Statistical analysis: Data were analyzed using the Statistical Package for Social Science (SPSS) version 16. The difference in mean DIS among NERD patients and controls was tested using independent t test. The association between categorical data and dilatation of intercellular space was tested using Chi-Square test. P-value of less than 0.05 was taken as significant. Results: Morphometric analysis performed on transmission electron microscopy microphotographs showed mean intercellular space diameter values of NERD patients were significantly ( two times) higher than that in normal controls (p<0.001). Intercellular space with width above > 0.93 μm is considered as dilated (cut-off value). There was strong association between dilated intercellular space with heartburn (p 0.001) and not with acid regurgitation (p 0.075). Conclusions: We can conclude that DIS at prickle cell layer is a promising diagnostic finding of early damage of esophageal epithelium.